CONFIDENCE AND MOTIVATION OF NOVICE ENGLISH TEACHERS AT VNU IN CONDUCTING RESEARCH - Lan, Le Thuy (VNU Journal of Foreign Studies, 2020)
The study aims to gain some insights into the confidence and motivation of young English teachers in doing research as a preliminary stage for further follow up research into the research practice of these teachers. The researcher opted for a qualitative approach by interviewing in person six novice English teachers working at a university in Vietnam National University, Hanoi. The outcomes show that the teachers had between low and medium confidence in their research ability and were motivated mainly by extrinsic factors such as school requirement while acknowledging the benefits research has on teaching practice and personal development.